Genome-wide association study of outcrossing in cytoplasmic male sterile lines of rice - Guo, Liang; Qiu, Fulin; Gandhi, Harish; Kadaru, Suresh; De Asis, Erik Jon; Zhuang, Jieyun; Xie, Fangming (Springer, 2017)
Stigma exsertion and panicle enclosure of male sterile lines are two key determinants of outcrossing in hybrid rice seed production. Based on 43,394 single nucleotide polymorphism markers, 217 cytoplasmic male sterile lines were assigned into two subpopulations and a mixed-group where the linkage disequilibrium decay distances varied from 975 to 2,690 kb. Genome-wide association studies (GWAS) were performed for stigma exsertion rate (SE), panicle enclosure rate (PE) and seed-setting rate (SSR). A total of 154 significant association signals (P < 0.001) were identified. They were situated in 27 quantitative trait loci (QTLs), including 11 for SE, 6 for PE, and 10 for SSR. It was shown that six of the ten QTLs for SSR were tightly linked to QTLs for SE or/and PE with the expected allelic direction. These QTL clusters could be targeted to improve the outcrossing of female parents in hybrid rice breeding. Our study also indicates that GWAS-base QTL mapping can complement and enhance previous QTL information for understanding the genetic relationship between outcrossing and its related traits.